Mathematical modeling of the role of bone turnover in pH regulation in bone interstitial fluid. (October 2021) - Poorhemati, Hossein; Komarova, Svetlana V.
Abstract: Background and aims: Bone turnover is strongly affected by pH of surrounding fluid, and in turn plays a role in maintaining systemic pH, however the quantitative contribution of bone processes to pH regulation is not known. Our goal was to develop a mathematical model describing pH regulation in the interstitial fluid and to examine the contribution of hydroxyapatite dissolution and precipitation to pH regulation. Materials and methods: We modeled twelve reversible equilibrium reactions of sixteen calcium, phosphate, hydrogen and carbonate species in the interstitial fluid and examined the buffering capacity and range. The effect of hydroxyapatite dissolution and precipitation was modeled by assuming that the calcium, phosphate and hydroxide contained in the bone volume adjacent to the interstitial fluid is instantaneously added to or removed from the interstitial fluid. Results: The carbonate buffer was found to dominate electrochemical buffering system of the bone interstitial fluid. Nevertheless, the phosphate added during dissolution of bone hydroxyapatite significantly improved the interstitial fluid buffering capacity. In contrast, hydroxyapatite precipitation had limited effect on the interstitial fluid pH regulation. Conclusion: This study provides mechanistic insights into the physicochemical processes underlying the known role of bone turnover processes in regulation of body pH homeostasis. Graphical Abstract: ga1 Highlights: We modeled how bone dissolution/precipitation affect interstitial fluid pH. Carbonate buffer dominated over phosphate buffer in the bone interstitial fluid. Hydroxyapatite dissolution improved interstitial fluid buffering capacity. pH regulation was mostly affected by phosphate associated with hydroxyapatite.